Aspects of a teacher’s mathematical knowledge in his orchestration of a discussion about rational numbers - Kleve, Bodil; Solem, Ida Heiberg (NOMAD Nordic Studies in Mathematics Education, 2014)
In this article we discuss how aspects of a mathematics teacher’s knowledge surfaced in a whole class discussion about decimal numbers, percentages and fractions. Our focus is the teacher’s orchestration of the discussion in order to unpack the mathematical content for the students. His interactive teaching which included questioning and probing students’ contributions in order to make the students take part in the discussion, were important features of this lesson. A range of aspects of the teacher’s mathematical knowledge was revealed in studying the teacher’s pedagogical moves, and we suggest that the interplay between the aspects of his knowledge was crucial in this lesson.